Studying the Rural in Education - Howley, Craig B. (Education Policy Analysis Archives, 1997)
This essay maintains that nation-building, partly through systems of schooling, has served rather more to debase than improve the rural circumstance. It suggests that a different logic of improvement is needed in rural education, but refrains from prescriptions. Instead, it focuses its attention on the sort of questions that researchers (and school improvers, for that matter) might ask to discover or invent that logic variously. It draws a distinction between cosmopolitan and local interests and provides examples of issues that exhibit the distinction. Finally, it suggests and provides hypertext links to sources in sociology, literature, philosophy, and education that might help educational researchers (and anyone else with an interest in "the rural") ground their studies and their actions in issues that honor rural interests. I remind readers that the very word "essay" means "tentative."